Analysis of the health level of syariah banking by camels methods on Pt. Bank Syariah Indonesia, Tbk (Case Study After Merger) - Syafira, Melinda; Zaki, Achmad (Institute of Computer Science (IOCS), 2024)
The aim of this research is to determine the health level of PT. Bank Syariah Indonesia, Tbk after the merger used the CAMELS method. The population of this study is the Annual Financial Report of Bank Syariah Indonesia, while the sample in this study is the Annual Financial Report 2021 – 2023 of Bank Syariah Indonesia after the merger. Data analysis technique uses the Camels Referring to Bank Indonesia Regulation No. 9/1/PBI/2007. The results of the research on BSI's asset quality ratio (KAP) show that it is good, the BSI Profitability Ratio shows that the resulting profitability is very good, the Capital Ratio shows that the capital owned by BSI is very strong, the Liquidity Ratio shows that BSI has problems paying its short-term obligations, the Sensitivity Ratio to market value reflects BSI BSI's consistency in covering exchange rates is very good. All of these indicators reflect the financial performance of PT. Bank Syariah Indonesia, Tbk is good, and can effectively and optimally support banking development to achieve the expected goals